Genetic factors associated with obesity risks in a Kazakhstani population - Madina Razbekova; Alpamys Issanov; Mei‐Yen Chan; Robbie Chan; Dauren Yerezhepov; Ulan Kozhamkulov; Ainur Akilzhanova; Chee–Kai Chan (BMJ, 2021)
Objectives There is limited published literature on the genetic risks of chronic inflammatory related disease (eg, obesity and cardiovascular disease) among the Central Asia population. The aim is to determine potential genetic loci as risk factors for obesity for the Kazakhstani population. Setting Kazakhstan. Participants One hundred and sixty-three Kazakhstani nationals (ethnic groups: both Russians and Kazakhs) were recruited for the cross-sectional study. Linear regression models, adjusted for confounding factors, were used to examine the genetic associations of single nucleotide polymorphisms (SNPs) in 19 genetic loci with obesity (73 obese/overweight individuals and 90 controls). Results Overall, logistic regression analyses revealed genotypes C/T in CRP (rs1205), A/C in AGTR1 (rs5186), A/G in CBS (rs234706), G/G in FUT2 (rs602662), A/G in PAI-1 (rs1799889), G/T (rs1801131) and A/G (rs1801133) in MTHFR genes significantly decrease risk of overweight/ obesity. After stratification for ethnicity, rs234706 was significantly associated with overweight/obesity in both Russians and Kazakhs, while rs1800871 was significant in Kazakhs only. Conclusions This study revealed that variations in SNPs known to be associated with cardiovascular health can also contribute to the risks of developing obesity in the population of Kazakhstan.